Deformation and Failure Mechanism of the Lower Roadway in a Close-Range Residual Coal Pillar Area - Wang, Xiao-He; Zhao, Zhi-Qiang; Wu, Zheng; Zhang, Hao-Hao; Wang, Jun; Sui, Yi; Ren, Zhi-Cheng (Frontiers in Earth Science, 2022)
The Tashan coal mine is selected as a case study to determine the deformation and damage mechanisms of the lower roadway in a close-range residual coal pillar area. Roof drilling peephole technology is applied to detect the damage to the roadway roof surrounding rock. A boundary invisibility equation is derived for the plastic zone of a circular hole based on the theory of a butterfly plastic zone in a non-uniform stress field in which the principal stress occurs at an arbitrary angle to the vertical. Maple mathematical drawing software is combined with FLAC3D numerical simulations to investigate the influence of the principal stress ratio and direction on the roadway plastic zone. The results indicate that the plastic zone of the roadway surrounding rock assumes a butterfly shape when the bidirectional stress ratio is large, and the direction of the butterfly-shaped failure of the roadway is related to the principal stress direction. Field test images are combined to show that the asymmetric damage pattern of the lower roadway in a close-range residual coal pillar area is influenced by the presence of the roadway in a non-uniform stress field in which the main stress direction is deflected.